Faces and Photography in 19th-Century Visual Science. (September 2016) - Wade, Nicholas J.
Reading faces for identity, character, and expression is as old as humanity but representing these states is relatively recent. From the 16th century, physiognomists classified character in terms of both facial form and represented the types graphically. Darwin distinguished between physiognomy (which concerned static features reflecting character) and expression (which was dynamic and reflected emotions). Artists represented personality, pleasure, and pain in their paintings and drawings, but the scientific study of faces was revolutionized by photography in the 19th century. Rather than relying on artistic abstractions of fleeting facial expressions, scientists photographed what the eye could not discriminate. Photography was applied first to stereoscopic portraiture (by Wheatstone) then to the study of facial expressions (by Duchenne) and to identity (by Galton and Bertillon). Photography opened new methods for investigating face perception, most markedly with Galton's composites derived from combining aligned photographs of many sitters. In the same decade (1870s), Kühne took the process of photography as a model for the chemical action of light in the retina. These developments and their developers are described and fixed in time, but the ideas they initiated have proved impossible to stop.